An evolving plug-and-play business infrastructure for networked organisations. (14th April 2009) - Rabelo, Ricardo J.; Gusmeroli, Sergio; Nagellen, Thierry; Arana, Cristina
This paper introduces a distributed and open ICT infrastructure that has been developed in a research project to help members of Collaborative Networks in doing businesses and collaborations together more efficiently. ICT-I design relies on the service oriented architecture paradigm and its services are to be used under the on demand and pay-per-use models. It is flexible to support an easy entrance of new services, offering supporting services for Virtual Breeding Environments, Virtual Organisations and Professional Virtual Communities. This paper details the ICT-I requirements, its architecture and services, and implementation issues. Conclusions and challenges are presented in the end.